Mobilizing National Identity and Othering Practices as Means of Resistance - Baikovich, Avital; Wasserman, Varda (Organization Science, 2020)
This paper explores the everyday practices, forms, and means by which employees mobilize national identity as a tool of resistance in opposing managerial demands of their dual, global/Western and local/Japanese, organizational identity. Drawing on an ethnographic study of a Japanese subsidiary of a multinational corporation, we show how employees use national identity to invoke three forms of othering in constructing various resistant identities: individual employees’ resistant identities through verbal othering, expressed in employees’ talk; departmental resistant identities through spatial othering, referring to employees’ use of space; and subsidiary resistant identity through ritual othering, illustrating employees’ collective use of ritual practices and symbolic artifacts. Our study makes three significant theoretical contributions: First, by illustrating the ways and means by which employees take on different national identities to construct diverse and often contradictory resistant identities to their expected dual organizational identity, we highlight the changeable nature of national identity. Second, this study contributes to our understanding of contextual constituents that shape individuals’ identity-related resistance. By unraveling employees’ various resistance forms, we show how resistance dynamically takes on assorted manifestations according to the organizational level in which it occurs and the managerial demands being resisted. Third, we illustrate the constitutive resources of resistance by highlighting the diverse means used by employees to construct their resistant identities.